Recent Advances in the Tandem Difunctionalization of Alkynes: Mechanism-Based Classification - Gao, Biwen; Deng, Danfeng; Huang, Dayun; Sun, Xiangyu (Synthesis, 2021)
Recent advances on the tandem difunctionalization of alkynes in the last decade (2010–2020) are summarized into five categories based on the type of mechanism: (1) radical addition and coupling for the synthesis of polysubstituted ketones and alkenes, (2) electrophilic addition of alkynes, (3) reactions mediated by haloalkynes or copper acetylides, (4) the preparation of cyclic compounds via radical processes, palladium-catalyzed reactions or conjugate additions, and (5) cyclic compounds as intermediates in ring openings. Herein, radical, electrophilic and nucleophilic reactions are discussed in detail. We hope this review will help to promote future research in this area. 1 Introduction2 Radical Addition and Coupling3 Electrophilic Addition4 Reactions Mediated by Haloalkynes or Copper Acetylides5 Cyclization6 Cyclization and Ring Opening7 Conclusions
Keywords: alkynes; difunctionalization; mechanism; radicals; tandem reactions